Bibliometric Analysis on Child Labor Using VoS Viewer and Biblioshiny: A Study on Scopus Database from 1902-2025 - Niswatin Nurul Hidayati; Rahma Sugihartati; Titik Puji Rahayu (Khazanah Sosial, 2025)
Child labor continues to be one of the most urgent global issues, highlighting ongoing social, economic, and ethical dilemmas that cross national and disciplinary lines. In spite of numerous international policy efforts and advocacy over the years, millions of children around the globe still endure exploitation in different types of labor, which has significant consequences for their rights, education, health, and future development. Grasping the progression of academic focus on this matter is essential, not only to chart current understanding but also to pinpoint gaps and emerging avenues for research that can guide effective interventions. This study presents a comprehensive bibliometric analysis of global scholarly publications on child labor from 1902 to 2025. Drawing on a Scopus dataset of 1,831 documents extracted from 815 publication sources, this research employs Biblioshiny and VOSviewer to analyze trends, authorship, institutional contributions, country participation, and thematic evolution within the literature. The findings reveal a steady yet accelerated growth in academic interest, particularly from the 1990s onward, coinciding with rising global awareness of children’s rights, poverty, and education. Despite a moderate average annual growth rate of 1.53%, the field has diversified significantly, encompassing themes such as economic development, social policy, gender, and child welfare. The most influential publications are rooted in development economics and social studies, with increasing contributions from journals focused on sustainability, ethics, and education. Prominent scholars and institutions, mainly from the United States and the United Kingdom, have dominated the field, though contributions from the Global South remain underrepresented. Emerging thematic trends include the intersection of child labor with technological change, digitization, and climate vulnerability. However, several research gaps persist, particularly in gender-disaggregated analysis, sector-specific studies, localized and longitudinal impact assessments, and theoretical integration across disciplines. The study highlights the need for future research to adopt interdisciplinary, inclusive, and forward-looking approaches that engage with the evolving realities of child labor, especially in light of digital economies, global crises, and systemic inequalities. These insights aim to inform more equitable and effective policy responses to the persistent global challenge of child labor.